Teachers Teaching Teachers: The Role of Workplace Peer Effects in Financial Decisions - Maturana, Gonzalo; Nickerson, Jordan (Review of Financial Studies, 2019)
This paper studies the role of workplace peers in the transmission of information pertinent to an important household financial decision: the mortgage refinancing choice. Exploiting commonalities in teaching schedules of school teachers in Texas to identify peer groups, we find that refinancing activity among teachers’ peers increases their likelihood of refinancing by 20.7%. The effect of peers increases with the potential savings realized upon refinancing and is stronger among younger teachers. Peers also affect teachers’ choice of lender. Overall, our findings suggest that peer interactions greatly reduce a household’s cost of acquiring and processing financial information. Received March 6, 2017; editorial decision July 31, 2018 by Editor Itay Goldstein. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.